Pengaruh Media Sosial Terhadap Pengembangan Komunikasi Bisnis di Shopee - Indri Sri Asdini; Azahra Salwa; Sylvia Amanda; Danny Ajar Baskoro; Lenti Susana Saragih (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the influence of social media on business communication development in Shopee. Through online surveys and interviews, data were collected from 100 respondents and 30 randomly selected consumers. The analysis results indicate that Shopee's communication strategy through social media is effective in enhancing customer interaction and influencing purchasing decisions. Positive responses to content, content influence on purchases, and Shopee's responsiveness to consumer interactions serve as evidence of the success of these strategies. The implications of these findings emphasize the importance of investing in innovative content development and training for social media response teams.